STRATEGI PEMASARAN UMKM DI TENGAH PANDEMI COVID-19 (STUDI KASUS PADA BENETREE COFFEE, DENPASAR) - Ni Ketut Lasmini; Ni Ketut Narti; Ida Bagus Sanjaya; KD Nindiana Widiantari (Forum Manajemen STIMI Handayani Denpasar, 2022)
This study aims to determine the company's strengths, weaknesses, opportunities, and threats and to find out the right marketing strategy to be applied to Benetree Coffee. The research was conducted for 3 months, starting from January - March 2021 at Benetree Coffee. The research method used is descriptive qualitative and quantitative. While the analytical tools used are SWOT analysis with IFAS (Internal Factor Analysis Summary) matrix, EFAS (External Factor Analysis Summary) matrix, IE matrix (Internal External), SWOT matrix. The results of the IFAS matrix analysis are 2.897 which indicates that the company's internal position is strong. The results of the EFAS matrix analysis are 2,774. The results of the mapping on the IE matrix show that Benetree Coffee in the marketing strategy occupies position V. This indicates that Benetree Coffee is in a growth position. The results of the SWOT matrix show that there are 11 alternative strategies that can be done by company.